Rainfall estimation for the south shore of the Mediterranean Sea using MSG infrared images - Tebbi, Mohsene Abdelfettah; Haddad, Boualem (International Journal of Intelligent Systems and Applications in Engineering, 2015)
The objective of this paper is the estimation of rainfall over the Algerian territory using MSG (Meteosat Second Generation) infrared data. To achieve this aim, we applied a calibrated GPI (GOES Precipitation Index) approach. This technique is tested to the complex situation of the Mediterranean climate. The rainfall estimated is obtained by using an affectation of adapted rain rates for a brightness temperature. These rain rates are determinate by analysing two years of in situ measures. The tests have been concluded during the rainy months January, February, and September of 2006/2007. The results show a good correlation between measured and estimated rainfall in winter and summer where stratiform and convective cells are present.